VOLUME GAINS, MARGIN COSTS: PANEL EVIDENCE ON THE COMPOSITION EFFECTS OF A UNIFORM SALES INCENTIVE IN B2B LIGHTING DISTRIBUTION - Syarippudin Syarippudin; Imanuddin Hasbi; Agus Maolana Hidayat (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Direct incentive programs from a brand manufacturer to a distributor's sales force are uncommon in the Indonesian B2B lighting sector, and their consequences for portfolio composition and distributor profitability have not been empirically tested. This study examines whether a flat 3 percent quarterly bonus, applied uniformly across a portfolio of more than three hundred products spanning a 600-fold price range, produces unintended consequences beyond its stated goal of volume growth. A sequential explanatory mixed-methods design is used. The quantitative phase analyses 781 product-quarter observations covering 326 products over eleven quarters from mid-2023 through end-2025. The qualitative phase uses confirmatory interviews with seventeen informants from distributor management and sales teams. The incentive program successfully drives all four sales performance dimensions measured in the study, covering volume growth, revenue share, transaction frequency, and a cumulative growth index, all of which are statistically significant. However, higher-priced products attract significantly fewer transactions per quarter and grow more slowly over time. Seven of eight hypotheses are supported. Qualitative findings confirm that the incentive effect adds to total selling activity rather than redirecting it, but transaction attention consistently concentrates on lower-priced products across the eleven-quarter period. The study extends agency theory to a three-party setting and provides the first panel-level evidence of composition effects from a uniform sales incentive in Indonesian B2B distribution.